Phase diagram of a continuous opinion dynamics on Barabasi–Albert networks. (9th March 2020) - Alves, T F A; Alves, G A; Lima, F W S; Macedo-Filho, A
Abstract: We consider the Biswas–Chatterjee–Sen model on Barabasi–Albert networks. This system undergoes a continuous phase transition from a consensus state to a disordered state by increasing a noise parameter q over a critical threshold q c . The noise parameter is defined as the probability of the affinity between two neighbors being negative, modeling Galam contrarians. We obtained the critical exponent ratios, , and by finite-size scaling data collapses, as well as the critical noises. Our numerical data is consistent with the critical thresholds q c being a linear function of the inverse of network connectivity z, and with an asymptotic value of q c = 0.3418, close to the value of the critical noise for the complete graph.